Produk Hukum Islam dan Implementasinya di Indonesia - Kurniawan, Muhammad Zuhud; Alwi, Mujahid; R., Abdurahman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this study is to analyze Islamic legal products and their implementation in Indonesia. This research is qualitative research with the type of library research. The data collection method used in this research is literature study. This research focuses on Islamic legal products. This research aims to find out how Islamic legal products are applied to Indonesian society as a whole, such as fiqh, fatwas, legal decisions and legislation. Apart from that, this research also aims to assess the feasibility and impact of implementing Islamic regulations in Indonesia, including the difficulties and opportunities that have existed so far.